Saberes que constituem a significação da terra no discurso dos atingidos por barragens hidrelétricas no Rio Grande do Sul durante a década de 70 - PASSOS, Lucilene dos Santos (2022)
In an attempt to stop the impacts of the world oil crisis during the 70's, the Brazilian government saw great potential in the rivers for the construction of hydroelectric plants. With the project to install dams in Rio Grande do Sul and Santa Catarina, those affected begin a movement to demand the collection of resettlement plans and compensation payments. This article examines, under the theoreticalanalytical light of materialist discourse analysis, the knowledge that indicates regularities that converge in the constitution of the discursive formation that demands from the State the reimbursement of flooded properties. The theoretical foundation is constituted from the readings in Orlandi (2005) and Michel Pêcheux (1970) mobilizing the theoretical edifice of Discursive Formation, the Corpus is constituted by the materialities cut out in bulletin nº 2 produced by the Regional Commission of People Affected by Dam (CRAB) , in 1982.